2013
DOI: 10.1371/journal.pone.0065385
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies and Sjogren’s Syndrome in Multiple Sclerosis, a Reappraisal

Abstract: BackgroundRheumatologic diseases may cause neurologic disorders that mimic multiple sclerosis (MS). A panel of serum autoantibodies is often obtained as part of the evaluation of patients suspected of having MS.ObjectivesTo determine, in light of recently revised diagnostic criteria for MS, neuromyelitis optica, and Sjogren’s Syndrome, if testing for autoantibodies in patients with a confirmed diagnosis of MS would reveal a frequency or demonstrate a clinical utility divergent from previous reports or lead to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 39 publications
1
16
3
Order By: Relevance
“…This finding was much different from previous studies in MS that identified SSA/SSB [30] and the finding of SSA/SSB in this study was very similar to NMO [31]. Moreover, the incidences of BON and ION with SSA/SSB were similar to MS in previous studies [32]. SS was a systemic autoimmune disease that presents with sicca symptomatology of the main mucosal surfaces and gland inflammation, and often presented with other immunological diseases [33].…”
Section: Discussioncontrasting
confidence: 99%
“…This finding was much different from previous studies in MS that identified SSA/SSB [30] and the finding of SSA/SSB in this study was very similar to NMO [31]. Moreover, the incidences of BON and ION with SSA/SSB were similar to MS in previous studies [32]. SS was a systemic autoimmune disease that presents with sicca symptomatology of the main mucosal surfaces and gland inflammation, and often presented with other immunological diseases [33].…”
Section: Discussioncontrasting
confidence: 99%
“…Coexisting autoimmune disorders, as well as sero-autoantibodies, were significantly more common in seropositive patients; SS and SLE were the most common CTDs and SSA and SSB were the most common autoantibodies in these patients. These findings are similar to previous studies which found that NMO could coexist with CTDs [43], particularly SS [44]; however, this association is rare in MS [45,46], as the prevalence of MS with SS ranges from 0 to 3.3 % [47]. Since AQP-4 Ab is a sensitive bio- CSF findings in NMO have been found to differ significantly from those of classical MS [48,49].…”
Section: Discussionsupporting
confidence: 90%
“…Besides, while the prevalence of Sjögren's syndrome in society is between 1% and 5%, this rate was found to be 0.9% in the present study (15). These results contradict the previous studies, which have demonstrated that Sjögren's syndrome is more frequent in MS patients, but they are similar to the ratios found out in the study carried out by Solomon et al on MS patients (14).…”
Section: Discussioncontrasting
confidence: 99%